Clinical Pharmacokinetics and Safety of a New HIV-1 Capsid Inhibitor, VH4004280, After Oral Administration in Adults Without HIV - Nilay Thakkar; Rulan Griesel; Amy Pierce; Veronica Bainbridge; Bronagh Shepherd; Konstantinos Angelis; Andrew Tomlinson; Yash Gandhi; Darin Brimhall; Daijha Anderson; Susan Andrews; Carolina Acuipil; et al. (Infectious Diseases and Therapy)
Abstract Introduction The pharmacokinetics, drug–drug interaction potential, and safety of a new HIV-1 capsid inhibitor, VH4004280 (VH-280), are described in this first-time-in-human study. Methods This randomized, double-blind, placebo-controlled, phase 1 study assessed oral VH-280 in adults without HIV. In parts 1 and 3, VH-280 was administered as powder-in-bottle (PiB) and tablet formulations, respectively, in single ascending doses. In part 2, VH-280 was administered as a PiB formulation once daily for 14 days in multiple ascending doses. In addition, in part 2, the effect of VH-280 on cytochrome P450 3A (CYP3A) activity was evaluated using midazolam as a probe substrate. Results In total, 73 participants were included (VH-280, n = 57; placebo, n = 16). Plasma exposures for VH-280 were broadly dose-proportional, and median time to maximum observed concentration was 9.0–17.0 h for the PiB and tablet formulations. Geometric mean terminal half-life was 145.8–207.8 h (> 6 days). Compared with PiB, exposures for the tablet formulation were 45–56% lower. Concomitant administration of midazolam after single and multiple doses of VH-280 did not result in clinically significant changes in midazolam or 1-hydroxymidazolam exposures; therefore, VH-280 is not anticipated to inhibit or induce CYP3A4. VH-280 was well-tolerated. Frequency of adverse events (AEs) was comparable between placebo and VH-280 groups. Adverse events related to VH-280 were primarily grade 1. There were no serious AEs, AEs leading to withdrawal from drug or study, or deaths. No trends in vital signs, electrocardiograms, or laboratory hematology parameters were observed, and there were no clinically relevant changes in chemistry parameters. Conclusions Data from this first-time-in-human study further characterize the pharmacokinetics of VH-280 after oral administration, providing support for the development of new capsid inhibitors as part of a complete long-acting regimen for the treatment and prevention of HIV-1. Clinical Trial Registration ClinicalTrials.gov, NCT05163522.